Strongmen of Political Party at Local Level: A Case Study on Fight between Blater and Lora Elites in Partai Amanat Nasional in Malang, Indonesia - JAINURI JAINURI; SOLAHUDIN SOLAHUDIN (Jurnal Studi Pemerintahan, 2017)
The study aims to describe the political party’s local elite in Malang, East Java, Indonesia. Previous researchers found out that there were variation, relation and interaction among political elites at the local level. In Malang, a district of East Java Province, there are some local power of politics in practice namely Blater elite and Lora elite. Blater is a group of local strongmen who has strong collabo- ration with the elite oligarchy at the level local. Both of them have done unfair practice of nepotism in the field of politics to achieve power of Partai Amanat Nasional (PAN) at the local level. On the other hand, Lora elite is a group of local strongmen, working together in synergy with the democratic elite to have access to power of the political party. In short, both of the political elites have been competitive to get the power of PAN. The following are the findings of the research:1) The existence of political party strongmen shows that the capacity of indi- vidual of the elites has the authority to determine various power context of the political party; 2) In the context of power, the existence of political party strongmen can limit and reduce the implementation of the political party regulation in the internal dynamics of the local inner circle of political party; and 3) Close relations depends upon a symbiotic relationship and the expression of mutual interest between the strongmen blater and the oligarchy so that patron-client relation could take place.